2008
DOI: 10.1074/jbc.m806115200
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Analysis of a Glycoside Hydrolase Family 97 Enzyme from Bacteroides thetaiotaomicron

Abstract: SusB, an 84-kDa ␣-glucoside hydrolase involved in the starch utilization system (sus) of Bacteroides thetaiotaomicron, belongs to glycoside hydrolase (GH) family 97. We have determined the enzymatic characteristics and the crystal structures in free and acarbose-bound form at 1.6 Å resolution. SusB hydrolyzes the ␣-glucosidic linkage, with inversion of anomeric configuration liberating the ␤-anomer of glucose as the reaction product. The substrate specificity of SusB, hydrolyzing not only ␣-1,4-glucosidic link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
95
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(112 citation statements)
references
References 40 publications
7
95
0
Order By: Relevance
“…7 The initial velocity of the formate ion-mediated reaction was also measured with alternative 8 acceptor substrates, including galactose, glucose, xylose, maltose, and cellobiose. These acceptors 9 followed equation 2 with the exception of galactose, with no increase in the velocity of fluoride 10 release observed for galactose. The constants α, β, and γ for the glycosyl acceptors are 11 summarized in Table 3.…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…7 The initial velocity of the formate ion-mediated reaction was also measured with alternative 8 acceptor substrates, including galactose, glucose, xylose, maltose, and cellobiose. These acceptors 9 followed equation 2 with the exception of galactose, with no increase in the velocity of fluoride 10 release observed for galactose. The constants α, β, and γ for the glycosyl acceptors are 11 summarized in Table 3.…”
mentioning
confidence: 89%
“…The NMR spectra indicated that the trisaccharide 6 was β-lactosyl α-D-galactopyranoside [α-D-Galp-(1↔1)-β-D-Glcp-(4←1)β-D-Galp; Gal-Lac], 7 which respective occupancies of β-glucosyl and β-galactosyl moieties at subsites +1 and +2 8 formed. The α-(1↔1)-β linkage was determined by the HMBC-correlation between H-1 (J = 8.2 9 Hz) of the glucose residue and C-1 of the galactose residue, and that between H-1 (J = 3.8 Hz) of 10 the galactose residue and C-1 of the glucose residue (Fig. 4C).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The enzyme (1.8 units/ml) was incubated with 7.5 mM 4-nitrophenyl ␣-glucopyranoside in 5 mM sodium phosphate buffer (pH 8.0) at 30°C for 20 min. The anomeric form of glucose produced by the reaction was analyzed by HPLC using a previous report procedure (32).…”
Section: Methodsmentioning
confidence: 99%